Antidiabetic effects of Brugmansia aurea leaf extract by modulating the glucose levels, insulin resistance, and oxidative stress mechanism - Fatima, Nisar; Anwar, Fareeha; Saleem, Uzma; Khan, Aslam; Ahmad, Bashir; Shahzadi, Irum; Ahmad, Hammad; Ismail, Tariq (Frontiers in Nutrition, 2022)
Ethnopharmacological relevance: Genus Brugmansia belonging to Solanaceae family has been traditionally used for anti-inflammatory, skin infections, wound healing and body aches in many different continents of the world. The current study aimed to investigate the potential benefits of methanolic extract of Brugmansia aurea in the management of diabetes and its underlying complications in alloxanized induced diabetic rats. Materials and methods: Animals were divided into nine groups (n = 6) in which four groups received different standard oral hypoglycemic agents and the other three groups received B. aurea leaf extract at dosing levels of 100, 200 and 400 mg/kg for 6 consecutive weeks and remaining two were normal and disease control groups. All groups except normal control received alloxan (150 mg/kg) and the animals whose glucose levels were raised to 200mg/dL were selected for the study. After the dosing period of 6 weeks, various biochemical parameters along with HbA1c, antioxidant profile, oral glucose tolerance test (OGTT), insulin sensitivity, histopathology and insulin resistance were measured and compared with untreated diabetic group. Results: B. aurea leaf extract at dosing level of 400mg/kg showed potent antidiabetic activity by reducing blood glucose level (p<0.001) after 6 weeks of treatment. OGTT data showed that B. aurea exhibited significant glucose tolerance by showing significant (p<0.001) reduction in blood glucose 2 hours post treatment. Other tests showed that plant extract possesses significantly increased (p<0.001) insulin sensitivity and decreased (p<0.001) insulin resistance. Biochemical profile showed reduced triglyceride and cholesterol while antioxidant profile showed restoration of antioxidant enzymes in pancreas, kidney and liver of treated rats. Conclusion: The present study The present study indicated that crude extract of B. aurea increases insulin sensitivity, reduces hyperlipidemia in diabetic rates, which rationalizes the traditional medicinal use of this plant as an antidiabetic agent.